2021
DOI: 10.1002/eqe.3422
|View full text |Cite
|
Sign up to set email alerts
|

Structural health monitoring of a 32‐storey steel‐frame building using 50 years of seismic monitoring data

Abstract: The case study, Los Angeles 32‐storey residential building, has an exceptionally long seismic observation history, spanning 50 years (1971‐2020), during which it has experienced many earthquakes, some causing extensive damage in the metropolitan area. Records of 13 earthquakes are analyzed, including San Fernando of 1971, to find out if permanent loss of stiffness occurred in the structure since 1971 and to describe statistically its nonlinear elastic behavior, not related to damage. It is a rare example of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…The average shear-wave velocity 𝑐 𝑆 of the model (Gnd to 49th floors) was found to be 𝑐 𝑆 ≈150-160 m/s for both directions (with the NS direction being slightly stiffer), indicating almost symmetric lateral resistance in both transverse directions, consistent with its physical characteristics 4 and within the range observed in other steel moment frame buildings. 36,82 The variations of 𝑐 𝑆 along the height detected by fitting a multi-layer model were significant. The analysis revealed very large wave velocity between Gnd and 5th floors, consistent with the larger stiffness and smaller mass density in that part of the structure, as compared with the other parts (see discussion in Sections 4.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average shear-wave velocity 𝑐 𝑆 of the model (Gnd to 49th floors) was found to be 𝑐 𝑆 ≈150-160 m/s for both directions (with the NS direction being slightly stiffer), indicating almost symmetric lateral resistance in both transverse directions, consistent with its physical characteristics 4 and within the range observed in other steel moment frame buildings. 36,82 The variations of 𝑐 𝑆 along the height detected by fitting a multi-layer model were significant. The analysis revealed very large wave velocity between Gnd and 5th floors, consistent with the larger stiffness and smaller mass density in that part of the structure, as compared with the other parts (see discussion in Sections 4.1).…”
Section: Discussionmentioning
confidence: 99%
“…Later the method was applied to horizontal response recorded in buildings, in which case 𝑄 and the corresponding damping ratio 𝜁 = 1∕(2𝑄) represent the effect of overall attenuation of vertically propagating waves in the structure, for frequencies inside the passband of the impulse responses, that is caused by material damping, scattering from internal inhomogeneities, geometric spreading, and other factors. 10,36,82,86 If the structure is on rigid soil and the attenuation is solely due to viscous material damping with constant 𝑄, then the 𝜁 = 1∕(2𝑄) from Equation ( 67) would be equal to the modal damping ratios. However, in reality, the two estimates are not necessarily the same.…”
Section: Observed Transfer-functions and Impulse Response Functionsmentioning
confidence: 99%
“…Therefore, at least in theory, their seismic responses can be accurately approximated by using simple beam models. Since the pioneering work of Biot 13 and several key studies that followed, 14–17 there have been quite a few efforts wherein various beam models are devised or used to represent building structures—for relatively recent examples, see literature 18–25 …”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Biot 13 and several key studies that followed, [14][15][16][17] there have been quite a few efforts wherein various beam models are devised or used to represent building structures-for relatively recent examples, see literature. [18][19][20][21][22][23][24][25] As lateral systems of buildings are usually combinations of various types of structural elements/subsystems-such as frames, walls, and braces-researchers realized that a single shear or Bernoulli beam might not be adequate to capture the overall seismic response. In 1965, Osawa 26 introduced the concept of the coupling beam in which uniform shear and uniform flexure (Bernoulli) beams are connected with rigid lateral elements to have similar displacements.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded signal in buildings allows assessing their response to earthquakes and monitoring changes to their structural health (e.g., Rahmani et al, 2015;Rahmani and Todorovska, 2021). Past studies have demonstrated the relevance of assessing the building's fundamental period (Goel and Chopra, 1997), which is a key parameter for estimating the expected performance of buildings during earthquakes (Michel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%